Perbandingan Recall and Precision pada Sistem Temu Kembali Informasi Lama (Simpus) dan Baru (Simpustaka) di Perpustakaan Universitas Islam Indonesia - Suharti Suharti; Husna Amalina Sholihah (Universitas Sebelas Maret Library, 2025)
Libraries need to continually adapt to technological developments in order to remain relevant to their users. The presence of the Online Public Access Catalog (OPAC) is expected to facilitate access to library collections. In 1998, the Universitas Islam Indonesia Library launched an OPAC called Simpus. As user needs grew, the library migrated to SLiMS 9 Bullian in September 2024, with the new OPAC named Simpustaka. System evaluation is necessary to assess performance, which can be measured through recall and precision tests. This study aims to compare the recall and precision of the old OPAC (Simpus) and the new OPAC (Simpustaka). This study uses a descriptive method with a quantitative approach with samples selected from the most frequently searched subjects. Data was tabulated, analyzed, and interpreted to draw conclusions. The findings show that both OPACs demonstrate high effectiveness, with scores above 0.68. However, the new OPAC (Simpustaka) requires further optimization to maximize its usability for library users.